Актуальні проблеми стану надійності енергетичного обладнання теплових електростанцій - Громко, Я.; Когут, М.; Куновський, Г.; Ванкевич, П.; Харандюк, Т. (Видавництво Національного університету “Львівська політехніка”, 2004)
The work of power equipment in thermoelectric power stations is examined which is used for hard fuel crushing and feeding it in power state burn in boilers. Conclusions are as follows: for reliability increasing of mills tires shafts hammers of crushers and fans blades it is necessary to introduce new technologies of worm parts of surfaces and their strengthening at the stage of their manufacture by plants — suppliers.
Keywords: 631.363